University Budget Versus Students - Sorooshian, Shahryar; Yahaghi, Javad (Maejo University, 2017)
A vital pillar of today’s society is the creation of places that bring together the finest minds of the society with intent to sustain knowledge and disseminate it to the coming generations as well as other members of society, and to nurture fresh knowledge on a global level and/or in a particular framework of time, place, and circumstance. The relationship between obtaining new knowledge (research) and distributing it (knowledge and education transmission) is extensively endorsed. Comprehensively speaking, this relationship forms the basis of the university.